Report of the Committee on the Elimination of Discrimination against Women, Sixtieth Session - United Nations Department for General Assembly; Conference Management (United Nations, 2005)
Official records of the Report of the Committee on the Elimination of Discrimination against Women: Thirty-second Session (10-28 January 2005), Thirty-third Session (5-22 July 2005).